The Effect Of Short Intermittent Training It (running / Running-strength) On The Maximum Aerobic Speed (mas), Maximum Oxygen Consumption (v̇o2max) And Explosive Strength Of Lower Limbs In The U17 Handball Players. - Yakoub, BOUSSADIA; KHAROUBI , Mohamed Fayçal; Hadj, SEFIR (Journal of Sport Science Technology and Physical Activities, 2022)
This study aims to comparing the effect of short intermittent training "running" (ITr) and intermittent training "running-strength" (ITr-s) on aerobic-anaerobic performances: the maximum oxygen consumption (VO2max), maximum aerobic speed (MAS) and explosive strength of lower limbs of handball players. For this purpose, we used the experimental method on an intentional sample of (12) male handball players subdivided into two homogeneous experimental groups from Nadjm Djemila -Setif- for 6 weeks of training, and for data collection, we used the physical tests (Yo-Yo test and Sargent Jump test). After collecting the results and having treated them statistically, we conclude that the two intermittent training had almost the same effect on MAS and VO2max, while the effect of short ITr-s on explosive strength of the lower limbs was significant compared to the ITr, the study recommends using the ITr-s in the physical preparation process at the beginning of season in order to develop effectively both aerobic/anaerobic performances.